Seasonal migration and networks: Evidence on Moldova's labour exodus - Dennis Görlich; Christoph Trebesch (Review of World Economics, 2008)
Seasonal migration is an ever more important phenomenon worldwide, but has received little attention in empirical research. This paper investigates the choice of seasonal versus longer-term migration on a household level. We use data from Moldova, a country that is witnessing a massive emigration shock. Surprisingly, neither children nor marital status appear to influence the decision to leave seasonally or for longer periods. This suggests high social and emotional costs of emigration. We also find that existing local networks of seasonal migrants are unrelated to permanent migration choice. Generally, networks appear to have a stronger influence on migration probabilities in urban settings.
Keywords: 330; Migration; Seasonal Migration; Migration Network; Poverty; Moldova; Saisonarbeitskräfte; Auswanderung; Armut; Soziales Netzwerk; Soziale Lage; Motivation; Migranten; Schätzung; Moldawien